Risk-Based Green Devsecops: A Risk-Maturity Assessment Framework For Secure, Climate-Conscious Cloud Operations - Rath, Ashwini Kumar (Global journal of Business and Integral Security, 2026)
Software development and IT operations can have significant environmental footprints that are often overlooked. As organizations face new sustainability regulations and stakeholder pressures, there is a critical need to integrate “green” practices into DevSecOps workflows without sacrificing agility or security. This paper presents a Risk-Maturity Assessment Framework (RMAF) for Green DevSecOps that embeds ecological sustainability into DevSecOps risk management. RMAF enables organizations to assess their sustainability maturity across governance, process, technology, and culture dimensions, and provides a structured path for continuous improvement. The framework is aligned with emerging compliance requirements (e.g., EU CSRD) and corporate ESG goals, ensuring that DevSecOps teams can meet reporting obligations while improving efficiency. We outline the RMAF’s components, scoring methodology, and alignment with DevSecOps principles, and propose an evaluation approach via a small enterprise case study. The paper provides practical insights for integrating sustainability into software engineering practice, aligning with current policy mandates.